Education therapeutic for the treatment of patients with peripheral arterial disease - Piotrkowska, Renata; Dobosz, Marek; Halena, Grzegorz; Książek, Janina (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2011)
Obliterative atheromatosis is, in 98% of cases, the cause of chronic lower limbs ischemia. Facts from literature confirm an increasing morbidity rate of lower limbs obliterative atheromatosis. Prophylaxis includes eliminating risk factors of atheromatosis as well as these which negatively influence blood circulation in the limb. Thus, therapeutic education is a crucial factor in the treatment plan. The patient who is educated, motivated and performs self-examination has a chance of longer life and its good quality. The aim of the study is presenting a model of therapeutic education of patients with lower limbs atheromatosis and analyzing the range of education performed by the therapeutic team. Conclusions: 1. Therapeutic education of patients with peripheral atheromatosis should be based on a model, professional and individualized action and should begin on the moment of diagnosis. 2. The education should be performed by a professionally prepared therapeutic team.